1998
DOI: 10.1128/iai.66.12.5867-5875.1998
|View full text |Cite
|
Sign up to set email alerts
|

Role of NK Cells in Early Host Response to Chlamydial Genital Infection

Abstract: The cell-mediated immune response has been documented to be the major protective immune mechanism in mice infected genitally with the agent of mouse pneumonitis (MoPn), a biovar of Chlamydia trachomatis. Moreover, there is strong evidence to indicate that gamma interferon (IFN-γ) is a major effector mechanism of the cell-mediated immune response. Previous studies from this laboratory have also reported that the dominant cell population in the genital tract is the CD4 Th1 population. When experiments were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 28 publications
1
59
1
Order By: Relevance
“…IFN-c is central to the immune response to C. trachomatis. C. trachomatis-infected women have higher levels of IFN-c in endocervical secretions than uninfected women [15] and this has also been demonstrated in vivo in murine infection by Chlamydia muridarum [7,16]. Studies using antibody depletion of IFN-c, IFN-c gene knockout mice, or IFN-c receptor gene knockout mice have all shown that IFN-c has a significant role to play in immune defence against various species of chlamydiae [5,6,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-c is central to the immune response to C. trachomatis. C. trachomatis-infected women have higher levels of IFN-c in endocervical secretions than uninfected women [15] and this has also been demonstrated in vivo in murine infection by Chlamydia muridarum [7,16]. Studies using antibody depletion of IFN-c, IFN-c gene knockout mice, or IFN-c receptor gene knockout mice have all shown that IFN-c has a significant role to play in immune defence against various species of chlamydiae [5,6,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TLR3 deficiency in hOE cells resulted in the increased synthesis of CCL5 and the type III interferon IL-29 (IFNλ1) throughout infection, and IL-28A (IFNλ2) late in infection (Figures 6 and 7). Collectively, these data demonstrate a putative role for TLR3 in the acute phase of the innate immune response to Chlamydia that is known to occur early during infection in vivo ( 17, 3942 ), and that TLR3 has some role in modulating mediators of the adaptive immune response (43).…”
Section: Resultsmentioning
confidence: 72%
“…Besides, a potential role for NK cells in anti-chlamydial immunity during reinfection is suggested by their expression of CD16 or the FccRIII, which binds IgG for ADCC, and NK cells have been associated with Th1 development and early clearance of chlamydia in mice. 45 As the FcR de®ciency evaluated in this study [i.e. FccRI (CD64) and FcRcIII (CD16)] excludes the receptor for IgA (CD89), the role of the latter in mediating protection during a secondary infection is unclear.…”
Section: Discussionmentioning
confidence: 97%